COMPOSITIONS AND METHODS FOR T CELL ENGINEERING (2021)
The present disclosure relates to an engineered immune cell and use thereof. The present disclosure provides an engineered immune cell comprising a CAR or engineered TCR, which CAR or engineered TCR can comprise a first antigen binding domain and a second antigen binding domain. The engineered immune cells of the present disclosure, when administered into a subject, can inhibit the host immune cells such as T cells and/or NK cells and enhance the survival and persistence of the engineered immune cells in vivo, thereby exhibiting more effective tumor killing activity.